أثر الاستهلاك المستدام في حماية البيئة - دعاس, نورالدين (University of Eloued جامعة الوادي, 2022)
تنصب هذه الدراسة على وصف وتقييم جملة التهديدات والآثار السلبية الواقعة على البيئة من جراء عملية الاستهلاك البشري لمختلف السلع والمنتجات، وتبحث في مدى تأثير جمهور المستهلكين على تعزيز جهود حماية البيئة من خلال تغيير سلوكهم التقليدي في الاستهلاك وجعل الاستدامة أولوية وخيارا ممكنا، والعمل على التأثير في صناع القرار والمنتجين لدفعهم نحو تلبية الطلب على المنتجات المستدامة والصديقة للبيئة . إن العلاقة الوثيقة بين مفهومي الاستهلاك وحماية البيئة ستثبت صحة الفرضية المتعلقة بوجود فرصة حقيقية تتعلق بتحسين خياراتهم الداعمة للاستهلاك المستدام. This research study explores the threats and negative effects of human consumption of different products on the environment. It also investigates the extent of consumers’ influence in improving environmental protection by changing their traditional habits and prioritizing sustainable options instead; and eventually, encouraging decision-makers and producers to provide more sustainable and environmentally friendly products. The close relationship between the concept of consumption and environmental protection proves the validity of the research hypothesis on the existence of a real opportunity to enhance sustainable consumption .
The Impact of Sustainable Consumption on Environmental Protection
مقال
Keywords: الاستهلاك المستدام، حماية البيئة، التنمية الاقتصادية ، التنمية المستدامة، المنتج النظيف; Sustainable Consumption; Environmental Protection; Economic Development; Sustainable Development; Clean Product.